Trend analysis in all-India marine products export using statistical modelling techniques - Venugopalan, R; ., Prajneshu (Indian Journal of Fisheries, 2011)
Various statistical modelling techniques, viz. Polynomial function fitting approach, Non-linear mechanistic growth modelling approach and ARIMA time-series methodology are employed for describing the all-India marine products export during 1960-’61 to 1994-’95. The underlying assumptions are examined by statistically sound procedures. Attempts are made to develop the most suitable statistical model. The identified model is then used to forecast the marine products export for three more years